Transition to long period stacking ordered structures in Mg85Gd9Zn6 alloys from amorphous ribbons examined by synchrotron radiation scattering: Comparison with Mg85Y9Zn6 alloys. (October 2017) - Okuda, Hiroshi; Yamasaki, Michiaki; Kawamura, Yoshihito
Abstract: Transition from supersaturated hcp crystals containing solute clusters into long-period stacking ordered structure has been examined by in-situ synchrotron radiation measurements. Amorphous Mg85 Gd9 Zn6 alloy ribbons were heated at a constant speed of 10 K/s, and small-angle scattering and wide angle diffraction profiles were compared with those obtained for Mg85 Y9 Zn6 amorphous ribbons. Comparison of the developments of microstructures in the two alloys suggested that the key factor that triggers the structural phase transition from hcp to LPSO structure is temperature. Graphical abstract: